PERAN PENDIDIKAN KEWIRAUSAHAAN DALAM MEMBANGUN SIKAP KEMANDIRIAN PESERTA DIDIK DI SMA SELAMAT PAGI INDONESIA KOTA BATU - Rokhmawati, Atik; Surjiati, Endang; Nu Graha, Andi (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
Increasing students' independence through entrepreneurship learning is one way for students to be able to face changes in world globalization. However, these two things cannot immediately appear in a person, but need to be trained. So this research was conducted to look at the role of entrepreneurship education in developing students' independent attitudes at Selamat Pagi Indonesia High School, Batu City. This research aims to describe: 1) Knowing the entrepreneurial learning of students at Selamat Pagi Indonesia High School, 2) Knowing the development of the independent character of students at Selamat Pagi Indonesia High School based on entrepreneurship education. This type of research is case study research with a qualitative approach. Data collection methods are observation, documentation and interviews. Data validity using source triangulation. The resource persons in this research were economics teachers, student affairs teachers, religion teachers, guidance and counseling teachers and students. The results of this research provide conclusions including: 1) In managing entrepreneurship-based social studies learning, the Learning Implementation Plan (RPP) is prepared by integrating entrepreneurial values ​​in learning and assessment steps. In preparing the syllabus, add one column to integrate entrepreneurial values. 2) The independence of students at Selamat Pagi Indonesia High School, Batu City in entrepreneurship-based social studies learning, namely initiative, self-confidence and responsibility.